Estimation of hand forces and propelling efficiency during front crawl swimming with hand paddles - Gourgoulis, V.; Aggeloussis, N.; Vezos, N.; Kasimatis, P.; Antoniou, P.; Mavromatis, G. (Journal of Biomechanics, 2008)
The aim of the study was to investigate possible modifications caused by hand paddles in the relative contribution of the lift and drag forces of the hand and in the propelling efficiency, during front crawl swimming. Eight female swimmers swam 25 m with maximal intensity without paddles, with small (116 cm2) and with large paddles (268 cm2). Four cameras operating at 60 Hz were used to record the images and the Ariel Performance Analysis System was used for the digitisation. The results showed that, although during swimming with hand paddles the hand's velocity decreased, the greater propulsive area of the hand paddle caused an increase in the drag, lift, resultant and effective forces of the hand. However, the relative contribution of lift and drag forces on swimming propulsion was not modified, nor was the direction of the resultant force. Hand paddles also increased the propelling efficiency, the stroke length and the swimming velocity, mainly because of the larger propulsive areas of the hand in comparison with free swimming. However, the significant decrease of the stroke rate, might argue the effectiveness of hand paddle training, particularly when large paddles are used in front crawl swimming.